(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Carbofuran is a kind of carbamate pesticide commonly used on major crops. The degradation of carbofuran by V (IV)/H2O2 system was investigated. The degradation system was strongly influenced by the pH, and initial concentration of VO2+. The degradation efficiency of carbofuran at the difference pH with the initial concentration of VO2+ in system was observed. An initial carbofuran concentration of 10 mg L1 was 95% degraded within 10 min at pH 2.6 with original VO2+ concentration of 5×104 M. The decrease of TOC content was observed during the catalytic process and the removal percentage was obtained about 20% after 24 h. Furthermore, therefore, this process based on the catalytic reaction of VO2+ and VO2 +, and was responsible for the continuous production of hydroxyl radicals in such system. It has also proven that the degradation percentage increase when a little amount of L-ascorbic acid of 5×104 M was applied, the degradation increase up to 20% more at 10 min. A gas chromatography-mass spectrometry analysis showed the formation of seven products, on the basis of formation of time and its abounded, of all these intermediate products, a reaction mechanism path was submitted. Bangladesh J. Sci. Ind. Res. 50(3), 211-218, 2015